Isolation Hope and Threat of Mangrove Restoration Program in Bogowonto Lagoon, Yogyakarta - Indonesia (2002-2014) - Firaswan, Abdullah; Aryandari, Rindra; Reza, Akbar; Faizah, Nur; Rachman, Nur; Fitri Ramadhani, Aqmarina; Sulthon Andalas, Muhammad (KnE Life Sciences, 2017)
Bogowonto Lagoon has the largest mangrove ecosystem in southern coast of Yogyakarta, Indonesia. Several activities on mangrove restoration have been conducted to escalate this remnant mangrove forest area. Conversely, rapid increase of shrimp pond area become threat for mangrove ecosystem in Bogowonto lagoon since the early of 21st century. Hence, This study is aimed to investigate mangrove composition, distribution and abundance, progress of mangrove restoration program and shrimp pond extensification in 2002 to 2014. Conducted from April 2015 to May 2015, this research consists of several steps namely survey, vegetation analysis, literature study, sociological study using questionnaire, measurement of mangrove and shrimp pond area using Landsat 8 imageries and Arc GIS 10.1. We determined 15 sites along Bogowonto Lagoon using random sampling by quadratic plot (10 m × 10 m for tree, 5 m ×5 m for sapling) and total counts (for seedling). The result showed that there were seven species of mangrove and six species of associate mangrove. Rhizopora mucronata Lamb. was dominant in each growthform with clumped distribution. R. mucronata and Avicennia marina (Forssk.) Vierh. also dominate from backswamp to rivermouth. Satellite imageries revealed that there was a hope due to upward trends of mangrove area in last 12 yr (approximately 5 ha). However, the significant increase sof shrimp pond area (approximately 34 ha) surrounding mangrove area become current and future threat. Based on sociological study, most of people around Bogowonto Lagoon have high awareness, but less participated on mangrove restoration program. Besides, the river mouth covered by sand become another obstacle of it. Keywords: Bogowonto lagoon, mangrove restoration, shrimp pond, vegetation analysis